2012
DOI: 10.1039/c2ra20360j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic device response controlled by an in situ polymerized ionic liquid based gel electrolyte

Abstract: Polymer electrolytes were synthesized by two different approaches and applied to electrochromic devices based on electrodeposited tungsten oxide (WO 3) or poly(3,4-ethylenedioxythiophene) (PEDOT) films as the cathode, and a Prussian blue (PB) film as the anode. The first method involved the entrapping of an ionic liquid in a polymer host (poly(methylmethacrylate) or PMMA) and the second approach relied on the in situ thermal polymerization of methylmethacrylate (MMA) in the hydrophobic ionic liquid, yielding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…More details about device fabrication can be found in our previous report. 25 A transparent, pale blue colored device encompassing the electrolyte in the form of a gel was obtained and all the edges were sealed with epoxy. The device is hereaer referred to as the PPBP-PB device.…”
Section: Construction Of An Electrochromic Device With Ppbpmentioning
confidence: 99%
“…More details about device fabrication can be found in our previous report. 25 A transparent, pale blue colored device encompassing the electrolyte in the form of a gel was obtained and all the edges were sealed with epoxy. The device is hereaer referred to as the PPBP-PB device.…”
Section: Construction Of An Electrochromic Device With Ppbpmentioning
confidence: 99%
“…In the past, amorphous WO 3 was widely studied owing to fast electrochromic switching response arising from its large specific surface areas [4]. Electrochromic WO 3 films can be prepared by several methods such as sputtering, evaporation, chemical vapor deposition (CVD), pulsed laser deposition (PLD), sol-gel, electrochemical deposition, hydrothermal reaction, and layer-by-layer (LbL) fabrication [9][10][11][12][13]. Layer-by-layer deposition of polymeric thin films was developed by Decher et al wherein a substrate is immersed in alternating solutions of polycations and polyanions, resulting in linear film growth with the ultimate thickness being controlled by the number of bilayers deposited [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Among various EC materials such as WO 3 , MoO 3 , NiO and Nb 2 O 5 , WO 3 is one of the most extensively studied because of its useful EC properties. [7][8][9][10][11] The evaluation of EC materials is typically based on their coloration efficiency (CE), reliability, response time and durability (which measures how long the EC properties of the material can be sustained when cations are intercalated/deintercalated under a cyclically applied electrical bias). 12,13 Previous studies have shown that the crystal structure (crystalline or amorphous) and microstructure of tungsten oxide greatly inuence its EC properties.…”
Section: Introductionmentioning
confidence: 99%